Silent Mastoiditis Proceeding with Intracranial Complication: A Case Report - Betül Şahin; Ahmet Karavuş; Tarık Şapçı; Uğur Günter Akbulut (Turkish Archives of Otorhinolaryngology, 2003)

(untitled)
Silent mastoiditis has been used as a synonym for latent or masked mastoiditis in the literature, defines a subclinical infectious process in the mucosal layer and the osseous structure of the mastoid cells in spite of an intact tympanic membrane. With the widespread usage of wide-spectrum antibiotics, the incidence of classical mastoiditis presentation has decreased and the incidence of chronic and subclinically proceeding silent mastoiditis that creates life-threatening situations because of being overlooked, has increased. Simple mastoidectomy has been carried out to the two cases with intracranial complications that are diagnosed as silent mastoiditis using temporal bone computerized tomography and scintigraphy in our clinic and the diagnosis has been confirmed peroperatively. After getting over an otitis media infection, the patient should be followed up in case of a silent mastoiditis even though a medical therapy is given. The diagnosis should be confirmed with a scintigraphic examination thinking of a latent infection proceeding in the mastoid in the patients continuing to complain of unclear symptoms like hearing loss, fullness and slight pain in the ear and retroauricular over sensitivity.